Effects and the Possible Remedies of Students’ Truancy in Secondary Schools in Meru South Sub County, Kenya - Kanga, Benjamin Mugambi; Jagero, Nelson (Advances in Social Sciences Research Journal, 2015)
Truancy is deliberate absence from school on the part of learners without the knowledge and consent of parents or absence of learners from school for which no reasonable or acceptable excuse is given. Truancy is a major challenge in Kenyan secondary schools. Truancy may have adverse affect on students, the school and the society at large. The purpose of this study was to establish effects and the possible remedies of secondary school students’ truancy in Meru South District, Kenya. The study elicited views from principals, class teachers, counseling teachers and form two students, purposive and simple random sampling method was used to select 298 Form 2 students 8 Principal 8 counseling teachers and 8 class teachers. Questionnaire was used to collect data. Data was analyzed quantitatively and presented using frequency distribution table, bar charts and percentages. The study identified the effects of truancy as poor academic performance for the truants, their class and school, wastage of learning time, dropping out of school, poverty to the individual and family in future, involvement in delinquent behavior, family instability, social maladjustment and insecurity in the family. The suggestions for the remedies truancy were strengthening of peer, joint, group and individual counseling in secondary schools, involving parent and the surrounding school community in developing attendance and anti truancy policies, effectively monitoring of the truants, creating a friendly school culture, developing attractive co-curricular activities, holding regular motivation talks, organizing career guidance right from when students are in Form 1 and helping the students set and remain focused on clear goals in live.